Philanthropy in Psychological Perspective: A Multidisciplinary Review and Development Opportunities in Indonesia - Hidayat, Ahmad; Herawati, Icha; Rizal, Irfani; Adzana, Adietha Wiossy (UIR Press, 2026)
This study aims to explore psychological theories related to philanthropy and its potential development in Indonesia. Philanthropy is a unique human behavior in giving and has attracted the attention of researchers in psychology, economics, sociology, anthropology, and religious studies. This study employs a comprehensive literature review method to analyze a wide range of relevant sources. It identifies the application of psychological theories such as empathy, altruism, social piety, meaningful life, and prosocial behavior, which have been utilized in various philanthropic studies. The potential direction for further development lies in philanthropic research from an Indigenous or Indonesian Philanthropy perspective, as such studies would be deeply rooted in local culture and traditional values inherent in Indonesia.